A gelatin-based hydrogel with multi-level pore size structure and preparation method thereof
By designing multi-stage pore size structures in conductive hydrogels and reasonably selecting conductive materials, the problem of limited improvement in mechanical properties of existing conductive hydrogels is solved, and the high mechanical properties, excellent conductivity and good performance of gelatin-based hydrogels are achieved. Low temperature resistance.
Patent Information
- Application Number
- CN202410878870.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-07-02
AI Technical Summary
Existing conductive hydrogels have limitations in improving mechanical properties, especially the limited increase in tensile strength, which is difficult to meet the application needs of biomedical hydrogels.
Gelatin-based hydrogels with multi-stage pore size structure are composed of gelatin, methacrylic acid, initiator and conductive material. They are polymerized through ultrasonic treatment and ultraviolet light to form a three-dimensional framework structure and primary and secondary pore structures, conductive material For example, PEDOT:PSS, nano-silver, etc. are used to improve conductivity.
It significantly improves the mechanical properties, swelling resistance and conductivity of conductive hydrogels, with tensile strength reaching 2.35~2.65MPa, tensile strain of 630%~670%, conductivity of 10~20mS/cm, and ability to withstand -20 Low temperature below ℃.
Smart Images

Figure CN118638426B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of gelatin-based functional hydrogels, in particular to a gelatin-based hydrogel with a multi-level pore structure and a preparation method thereof. Background Art
[0002] Hydrogel is a type of polymer material system with a three-dimensional network structure formed by cross-linking hydrophilic polymer chains. It has been widely used in the biomedical field because of its extremely similar properties to the extracellular matrix. At the same time, due to the three-dimensional interconnected network pore structure inside the hydrogel, it has better water storage and moisture retention capacity and material exchange capacity, and its application potential in drug release, tissue repair, etc. has gradually become prominent. Therefore, it is widely used in tissue engineering, drug delivery systems, medical dressings, etc. in the biomedical field. Compared with traditional hydrogels, conductive hydrogels have the dual characteristics of hydrogels and conductive substances, and have the effect of promoting the repair of electrically sensitive tissues and promoting wound healing under electrical stimulation, so they show great application value in the biomedical field.
[0003] At present, there are mainly two types of conductive hydrogels: one is to implant microelectrodes in hydrogels to form composite conductive hydrogels; the other is to add conductive polymers, metal and metal oxide nanoparticles or conductive materials such as graphene, carbon nanotubes, and carbon nanosheets to hydrogels to prepare conductive hydrogels. The latter has been more widely studied and applied because it can more effectively conduct endogenous electrical stimulation and distribute it to biological tissues. However, due to the three-dimensional network structure of the hydrogel itself, it is difficult for the added conductive material to be evenly dispersed in the hydrogel and it is difficult to improve the mechanical properties. Therefore, how to improve the mechanical properties of conductive hydrogels to meet the application requirements of biomedical hydrogels is of great significance.
[0004] Patent document with publication number CN116217970A discloses a cold-induced high-strength conductive eutectic hydrogel and its preparation method and application. By introducing a low eutectic solvent DES in the preparation process, which forms a mixed solvent with water as a gel dispersion medium, the mechanical properties and weather resistance of the eutectic gel are improved, and the conductivity of the gel is increased. However, due to the limitation of the intrinsic properties of eutectic, the tensile strength of the prepared eutectic hydrogel is below 130kPa, and the improvement of mechanical properties is limited.
[0005] The patent document with publication number CN109627461A discloses a polypyrrole nanocomposite conductive hydrogel and its preparation method. The polypyrrole is modified by dopamine to obtain a polypyrrole nanomaterial. The nanomaterial can be well dispersed in the gelatin matrix material, and the hydrogen bonding between the hydrogel molecules is conducive to its stable existence. The prepared conductive hydrogel has excellent conductivity and stable chemical properties, and improves the mechanical properties of the hydrogel. However, the preparation process of this method is relatively complicated. It is necessary to modify the gelatin and prepare the polypyrrole nanomaterial first, and then initiate polymerization by ultraviolet light to obtain the polypyrrole nanocomposite conductive hydrogel. In addition, the tensile strength is limited and still remains below 0.13MPa.
[0006] In summary, there is an urgent need to develop a new type of conductive hydrogel with a simple preparation process and the ability to further improve the mechanical properties of the conductive hydrogel. Summary of the invention
[0007] The purpose of the present invention is to provide a gelatin-based hydrogel with a multi-level pore structure and a preparation method thereof, the preparation process is simple, and the mechanical properties of the conductive hydrogel can be further improved.
[0008] In the first aspect, the present invention provides a gelatin-based hydrogel with a multi-level pore structure, wherein the gelatin-based hydrogel is prepared from raw materials including gelatin, methacrylic acid, an initiator and a conductive material, wherein the mass ratio of the gelatin, methacrylic acid, the initiator and the conductive material is 5-30:5-50:0.0005-0.05:3-80, and the gelatin-based hydrogel includes a three-dimensional skeleton structure and a primary pore structure surrounded by the three-dimensional skeleton structure, and also includes a secondary pore structure, wherein the secondary pore structure is distributed on the three-dimensional skeleton structure, and the inner surfaces of the primary pore structure and the secondary pore structure are continuous and free of holes, the pore diameter of the primary pore structure is 30-100 μm, and the pore diameter of the secondary pore structure is 5-25 μm.
[0009] Optionally, the mass ratio of the gelatin, methacrylic acid, initiator and conductive material is 8-20:8-30:0.0008-0.03:8-40.
[0010] Optionally, the pore size of the primary pore structure is 30 to 80 μm, and the pore size of the secondary pore structure is 5 to 20 μm.
[0011] Optionally, the conductive material is at least one of PEDOT:PSS, nanosilver, carbon nanotubes, carbon nanosheets, MXenes or graphene.
[0012] Optionally, the initiator is at least one of 2-ketoglutaric acid, glutaraldehyde or ammonium persulfate.
[0013] Optionally, the gelatin-based hydrogel has a tensile strength of 2.35 to 2.65 MPa, a tensile strain of 630% to 670%, a balanced swelling ratio of 8% to 11%, and a conductivity of 10 to 20 mS / cm.
[0014] In a second aspect, the present invention provides a method for preparing a gelatin-based hydrogel with a multi-level pore structure, comprising the following steps:
[0015] S1. Preparation of stock solution: Weigh gelatin according to the mass ratio and dissolve it in deionized water to prepare a stock solution, wherein the mass ratio of gelatin to deionized water is 5 to 30:45 to 300;
[0016] S2. Preparation of a mixed solution: Weighing methacrylic acid, an initiator and a conductive material according to a mass ratio, and dissolving the methacrylic acid, the initiator and the conductive material in the stock solution to obtain a mixed solution, wherein the mixed solution is subjected to ultrasonic treatment, the frequency of the ultrasonic treatment is 30 to 50 khz, and the power of the ultrasound is 80 to 150 W;
[0017] S3. Preparation of hydrogel: The mixed solution after ultrasonic treatment is polymerized by ultraviolet light, and then immersed in an inorganic salt solution to prepare a gelatin-based hydrogel with a multi-level pore structure.
[0018] Optionally, in step S1, the gelatin is added to the deionized water, and stirred in a water bath at 40 to 60° C. for 0.3 to 6 h to allow the gelatin to be completely dissolved in the deionized water, thereby preparing the stock solution, and the stirring speed is 50 to 500 rpm / min.
[0019] Optionally, in step S2, the methacrylic acid is added to the stock solution, and stirred for 0.3-6 hours in a water bath at 40-60°C, with a stirring speed of 50-500 rpm / min, to prepare a premix A; the initiator is added to the premix A, and the stirring is continued for 0.3-6 hours in a water bath at 40-60°C, to prepare a premix B; the conductive material is added to the premix B, and the stirring is continued for 0.3-6 hours in a water bath at 40-60°C, to prepare the mixed solution.
[0020] Optionally, in step S3, the mixed solution is irradiated with the ultraviolet light of 300 to 400 nanometers for 50 to 100 minutes, and then immersed in the inorganic salt solution for 1 to 5 hours, and the concentration of the inorganic salt solution is 20 to 40 wt%.
[0021] In summary, the present invention has at least one of the following beneficial effects:
[0022] 1. The present invention provides a gelatin-based hydrogel with a multi-level pore structure. The gelatin-based hydrogel is prepared from raw materials including gelatin, methacrylic acid, an initiator and a conductive material. The gelatin-based hydrogel includes a three-dimensional skeleton structure and a primary pore structure surrounded by the three-dimensional skeleton structure, and also includes a secondary pore structure. The secondary pore structure is distributed on the three-dimensional skeleton structure, and the inner surfaces of the primary pore structure and the secondary pore structure are continuous and free of holes. The pore size of the primary pore structure is 30 to 100 μm, and the pore size of the secondary pore structure is 5 to 25 μm. The multi-level pore structure enables the gelatin-based hydrogel to have excellent mechanical properties, anti-swelling properties and conductive properties, and has good low temperature resistance. In subsequent embodiments, the tensile strength of the gelatin-based hydrogel is measured to be 2.35 to 2.65 MPa, the tensile strain is 630% to 670%, the equilibrium swelling ratio is 8% to 11%, the conductivity is 10 to 20 mS / cm, and it can withstand low temperatures below -20°C.
[0023] 2. The method for preparing a gelatin-based hydrogel with a multi-level pore structure provided by the present invention has the advantages of simple operation, large-scale preparation and low cost, and can be promoted on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a scanning electron microscope photograph of the cross section of the freeze-dried gelatin-based hydrogel prepared in Example 1;
[0025] Figure 2 It is a comparison picture of the mechanical properties of the hydrogels prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3;
[0026] Figure 3 This is a photograph of the appearance of the gelatin-based hydrogel prepared in Example 1 and the existing hydrogel after being stored at -20°C for 10 hours;
[0027] Figure 4 is a scanning electron microscope photograph of the cross section of the freeze-dried gelatin hydrogel prepared in Comparative Example 1;
[0028] Figure 5 is a scanning electron microscope photograph of the cross section of the methacrylic acid hydrogel prepared in Comparative Example 2 after freeze drying;
[0029] Figure 6 : is a scanning electron microscope photograph of the cross section of the gelatin-based hydrogel prepared in Example 3 after freeze-drying. DETAILED DESCRIPTION
[0030] The present invention provides a gelatin-based hydrogel with a multi-level pore structure and a preparation method. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] In some embodiments of the present invention, the present invention provides a gelatin-based hydrogel with a multi-level pore structure, wherein the gelatin-based hydrogel is prepared from raw materials including gelatin, methacrylic acid, an initiator and a conductive material, wherein the mass ratio of the gelatin, methacrylic acid, the initiator and the conductive material is 5-30:5-50:0.0005-0.05:3-80, and the gelatin-based hydrogel includes a three-dimensional skeleton structure and a primary pore structure surrounded by the three-dimensional skeleton structure, and also includes a secondary pore structure, wherein the secondary pore structure is distributed on the three-dimensional skeleton structure, and the inner surfaces of the primary pore structure and the secondary pore structure are continuous and free of holes, the pore diameter of the primary pore structure is 30-100 μm, and the pore diameter of the secondary pore structure is 5-25 μm.
[0032] In some embodiments of the present invention, the mass ratio of gelatin, methacrylic acid, initiator and conductive material is 5-20: 5-30: 0.0005-0.05: 5-50; preferably, the mass ratio of gelatin, methacrylic acid, initiator and conductive material is 8-20: 8-30: 0.0008-0.03: 8-40; more preferably, the mass ratio of gelatin, methacrylic acid, initiator and conductive material is 10-15: 10-15: 0.001-0.01: 10-20.
[0033] In some embodiments of the present invention, the pore size of the primary pore structure is 30-80 μm, and the pore size of the secondary pore structure is 5-20 μm; preferably, the pore size of the primary pore structure is 30-60 μm, and the pore size of the secondary pore structure is 5-20 μm.
[0034] In some embodiments of the present invention, the conductive material is at least one of PEDOT:PSS, nanosilver, carbon nanotubes, carbon nanosheets, MXenes or graphene; preferably, the conductive material is at least one of PEDOT:PSS, nanosilver, carbon nanotubes; more preferably, the conductive material is nanosilver.
[0035] In some embodiments of the present invention, the initiator is at least one of 2-ketoglutaric acid, glutaraldehyde or ammonium persulfate; preferably, the initiator is 2-ketoglutaric acid.
[0036] In some embodiments of the present invention, the tensile strength of the gelatin-based hydrogel is 2.35 to 2.65 MPa, the tensile strain is 630% to 670%, the equilibrium swelling ratio is 8% to 11%, and the conductivity is 10 to 20 mS / cm; preferably, the tensile strength of the gelatin-based hydrogel is 2.48 to 2.65 MPa, the tensile strain is 650% to 670%, the equilibrium swelling ratio is 8% to 10%, and the conductivity is 12 to 20 mS / cm.
[0037] In some embodiments of the present invention, the present invention provides a method for preparing a gelatin-based hydrogel with a multi-level pore structure, comprising the following steps:
[0038] S1. Preparation of stock solution: Weigh gelatin according to the mass ratio and dissolve it in deionized water to prepare a stock solution, wherein the mass ratio of gelatin to deionized water is 5-30:45-300; preferably, the mass ratio of gelatin to deionized water is 8-20:72-200; more preferably, the mass ratio of gelatin to deionized water is 10-15:90-150;
[0039] S2. Preparation of mixed solution: methacrylic acid, initiator and conductive material are weighed according to the mass ratio, and the methacrylic acid, initiator and conductive material are dissolved in the stock solution to obtain a mixed solution, the mixed solution is subjected to ultrasonic treatment, the frequency of the ultrasonic treatment is 30-50 khz, and the power of the ultrasound is 80-150 W; preferably, the frequency of the ultrasonic treatment is 35-45 khz, and the power of the ultrasound is 90-120 W; the time of ultrasonic treatment of the mixed solution is 0.1-3 h; preferably, the time of ultrasonic treatment of the mixed solution is 0.2-1 h.
[0040] S3. Preparation of hydrogel: The mixed solution after ultrasonic treatment is polymerized by ultraviolet light, and then immersed in an inorganic salt solution to prepare a gelatin-based hydrogel with a multi-level pore structure.
[0041] In some embodiments of the present invention, in step S1, the gelatin is added to the deionized water, and stirred for 0.3-6 hours in a water bath at 40-60° C. so that the gelatin is completely dissolved in the deionized water to prepare the stock solution, and the stirring speed is 50-500 rpm / min.
[0042] In some embodiments of the present invention, in step S2, the methacrylic acid is added to the stock solution, stirred for 0.3-6 hours in a water bath at 40-60°C, with a stirring speed of 50-500 rpm / min, to prepare a premixed solution A; the initiator is added to the premixed solution A, and the stirring is continued for 0.3-6 hours in a water bath at 40-60°C to prepare a premixed solution B; the conductive material is added to the premixed solution B, and the stirring is continued for 0.3-6 hours in a water bath at 40-60°C to prepare the mixed solution.
[0043] In some embodiments of the present invention, in step S3, after the mixed solution is irradiated with the ultraviolet light of 300 to 400 nanometers for 50 to 100 minutes, it is immersed in the inorganic salt solution for 1 to 5 hours, and the concentration of the inorganic salt solution is 20 to 40 wt%. Preferably, the inorganic salt solution includes one or more of ammonium sulfate solution, sodium chloride solution, etc.; more preferably, the inorganic salt solution is ammonium sulfate solution. The temperature of the immersion treatment in the inorganic salt solution is -20 to 20°C, preferably, the temperature of the immersion treatment is -5 to 5°C.
[0044] In step S3, the prepared gelatin-based hydrogel can withstand low temperatures below -20°.
[0045] The present invention is further described in detail below in conjunction with specific examples and comparative examples. The raw materials in the specific examples of the present invention are commercially available unless otherwise specified.
[0046] Example 1
[0047] This embodiment provides a preparation of a gelatin-based hydrogel, comprising the following steps:
[0048] S1. Preparation of stock solution: Weigh gelatin (G108396 gelatin, pharmaceutical grade, gelatin strength ~240gBloom, Shanghai Aladdin Biochemical Technology Co., Ltd.) and deionized water according to the mass ratio, the mass ratio of gelatin to deionized water is 10 parts:90 parts, add gelatin to deionized water, stir for 3 hours in a 40°C water bath to completely dissolve the gelatin in the deionized water, and stir at a speed of 200 rpm / min to prepare a stock solution;
[0049] S2. Preparation of mixed solution: methacrylic acid, initiator and conductive material are weighed according to the mass ratio. The mass ratio of gelatin, methacrylic acid (M434201, Shanghai Aladdin Biochemical Technology Co., Ltd.), initiator and conductive material in this embodiment is 10 parts: 10 parts: 0.001 parts: 10 parts. The initiator in this embodiment is 2-ketoglutaric acid (K105571, 98wt%, Shanghai Aladdin Biochemical Technology Co., Ltd.), and the conductive material is PEDOT:PSS (P191136, PEDOT:PSS mass ratio is 1:6, content is 1.5wt% soluble in water, Shanghai Aladdin Biochemical Technology Co., Ltd.), and the weighed methacrylic acid, initiator and conductive material are dissolved in the original solution of step S1 to obtain a mixed solution. Specifically, methacrylic acid was added to the stock solution prepared in step S1, and stirred for 2 hours in a water bath at 40°C, with a stirring speed of 200 rpm / min, to prepare a premixed solution A; 2-ketoglutaric acid was added to the premixed solution A, and the stirring was continued for 2 hours in a water bath at 40°C, to prepare a premixed solution B; PEDOT:PSS was added to the premixed solution B, and the stirring was continued for 1 hour in a water bath at 40°C, to obtain a mixed solution. The mixed solution was subjected to ultrasonic treatment for 0.3 hours, with an ultrasonic frequency of 40 khz and an ultrasonic power of 100 W.
[0050] S3. Preparation of hydrogel: After the ultrasonic treatment, the mixed solution is polymerized by ultraviolet light, and then immersed in an inorganic salt solution to prepare a gelatin-based hydrogel. The inorganic salt solution of this embodiment is an ammonium sulfate solution with a concentration of 30wt%. Specifically, the mixed solution after ultrasonic treatment in step S2 is poured into a polytetrafluoroethylene mold, exposed to ultraviolet light with a wavelength of 365 nanometers for 70 minutes at a temperature of 25°C for polymerization, and then immersed in an ammonium sulfate solution at a temperature of 0°C for 2 hours to finally prepare a gelatin-based hydrogel.
[0051] Microstructure testing:
[0052] Scanning electron microscopy (SEM) was used to characterize the microstructure of gelatin-based hydrogels. Figure 1 is a scanning electron microscope image of the cross section of the gelatin-based hydrogel finally prepared in step S3 of Example 1 after freeze drying. Figure 1 It can be seen that the gelatin-based hydrogel has a multi-level pore structure, which includes a three-dimensional skeleton structure and a primary pore structure surrounded by the three-dimensional skeleton structure (indicated by the red arrow), and a secondary pore structure (indicated by the blue arrow). The secondary pore structure is distributed on the three-dimensional skeleton structure, and the inner surfaces of the primary pore structure and the secondary pore structure are continuous without holes. The pore diameter of the primary pore structure is 40-80μm, and the pore diameter of the secondary pore structure is 5-20μm.
[0053] Anti-swelling performance test:
[0054] The gelatin-based hydrogel finally prepared in step S3 of Example 1 was freeze-dried and placed in a PBS buffer at 25° C. to allow the swelling to reach equilibrium. After the swelling of the gelatin-based hydrogel reached equilibrium, the surface moisture of the gelatin-based hydrogel was taken out and wiped dry. According to the formula: ESR = (W Es -W d ) / W d , calculate the equilibrium swelling ratio, W Es is the mass of gelatin-based hydrogel when it reaches equilibrium swelling, W d The equilibrium swelling ratio of the gelatin-based hydrogel prepared in Example 1 was measured to be 8%, which shows that the gelatin-based hydrogel prepared in Example 1 has excellent anti-swelling properties.
[0055] Mechanical properties test:
[0056] The gelatin-based hydrogel was subjected to a tensile test using a universal mechanical testing machine. The gelatin-based hydrogel finally prepared in step S3 of Example 1 was cut to prepare a tensile sample, and the tensile rate was 100 mm / min. The tensile stress and strain were calculated based on the initial cross-sectional area and initial length of the test sample. The tensile stress-strain curve of the gelatin-based hydrogel of Example 1 was measured as follows: Figure 2 As shown, the tensile strength of the gelatin-based hydrogel of Example 1 was measured to be 2.48 MPa, and the tensile strain was 650%. It can be seen that the gelatin-based hydrogel prepared in Example 1 has excellent mechanical properties.
[0057] Conductivity test:
[0058] The conductivity of the gelatin-based hydrogel was tested using a digital source meter. The gelatin-based hydrogel finally prepared in step S3 of Example 1 was cut to prepare a conductivity test sample, and the test sample was connected to the test port of the digital source meter. The electrical signal transmitted can be used to calculate the conductivity of the test sample. The calculation formula is: δ = L / RS, δ is the conductivity; L is the length of the test sample, S is the cross-sectional area of the test sample; R is the resistance. The conductivity of the gelatin-based hydrogel of Example 1 was measured to be 12mS / cm. It can be seen that the gelatin-based hydrogel prepared in Example 1 has excellent conductive properties.
[0059] Frost resistance test:
[0060] The hydrogel was stored at -20°C for 10 hours and then taken out to record the changes in the gelatin-based hydrogel. Figure 3 (a) is a photograph of the appearance of the gelatin-based hydrogel finally prepared in step S3 of Example 1, which is taken out after being stored in an environment of -20°C for 10 hours. It can be seen from the observation that the appearance of the gelatin-based hydrogel of Example 1 does not freeze and remains in its original state. Therefore, it can be seen that the gelatin-based hydrogel of Example 1 has excellent low-temperature resistance. Figure 3(b) is a photograph of the appearance of an existing gelatin hydrogel (G108396 gelatin, pharmaceutical grade, gel strength ~240g Bloom, Shanghai Aladdin Biochemical Technology Co., Ltd.) after being stored at -20°C for 10 hours and then taken out, showing that freezing has occurred.
[0061] Example 2
[0062] This embodiment provides a preparation of a gelatin-based hydrogel, comprising the following steps:
[0063] S1. Preparation of stock solution: Weigh gelatin (G108396 gelatin, pharmaceutical grade, gelatin strength ~240gBloom, Shanghai Aladdin Biochemical Technology Co., Ltd.) according to the mass ratio, the mass ratio of gelatin to deionized water is 10 parts:100 parts, add gelatin to deionized water, stir for 2 hours in a 50°C water bath to completely dissolve the gelatin in the deionized water, and stir at a speed of 300 rpm / min to prepare a stock solution;
[0064] S2. Preparation of mixed solution: Weigh methacrylic acid (M434201, Shanghai Aladdin Biochemical Technology Co., Ltd.), initiator and conductive material according to the mass ratio. The mass ratio of gelatin, methacrylic acid, initiator and conductive material in this embodiment is 10 parts: 15 parts: 0.01 parts: 15 parts. The initiator in this embodiment adopts 2-ketoglutaric acid (K105571, 98wt%, Shanghai Aladdin Biochemical Technology Co., Ltd.), and the conductive material adopts carbon nanotubes (C434649 single-walled carbon nanotubes, ≥96wt%, Shanghai Aladdin Biochemical Technology Co., Ltd.), and the weighed methacrylic acid, initiator and conductive material are dissolved in the original solution to obtain a mixed solution. Specifically, methacrylic acid was added to the stock solution prepared in step S1, and stirred for 1 hour in a water bath at 50°C, with a stirring speed of 300 rpm / min, to prepare a premixed solution A; 2-ketoglutaric acid was added to the premixed solution A, and the stirring was continued for 1 hour in a water bath at 50°C, to prepare a premixed solution B; carbon nanotubes were added to the premixed solution B, and the mixture was stirred for 0.3 hours in a water bath at 60°C, to obtain a mixed solution. The mixed solution was subjected to ultrasonic treatment for 0.3 hours, with an ultrasonic frequency of 40 khz and an ultrasonic power of 100 W.
[0065] S3. Preparation of hydrogel: After the mixed solution after ultrasonic treatment is polymerized by ultraviolet light, it is immersed in an inorganic salt solution to prepare a gelatin-based hydrogel. The inorganic salt solution of this embodiment is an ammonium sulfate solution with a concentration of 30wt%. Specifically, the mixed solution after ultrasonic treatment in step S2 is poured into a polytetrafluoroethylene mold, exposed to ultraviolet light with a wavelength of 365 nanometers for 70 minutes at a temperature of 25°C for polymerization, and then immersed in an ammonium sulfate solution at a temperature of 0°C for 2 hours to finally prepare a gelatin-based hydrogel.
[0066] The gelatin-based hydrogel finally prepared in step S3 of Example 2 was tested by the same test method as in Example 1. It was found that the gelatin-based hydrogel finally prepared in step S3 of Example 2 was a multi-level pore structure, which included a three-dimensional skeleton structure and a primary pore structure surrounded by the three-dimensional skeleton structure, and also included a secondary pore structure, which was distributed on the three-dimensional skeleton structure, and the inner surfaces of the primary pore structure and the secondary pore structure were continuous and free of holes, the pore size of the primary pore structure was 50-100 μm, and the pore size of the secondary pore structure was 10-25 μm. The gelatin-based hydrogel of Example 2 was found to have a balanced swelling rate of 11%, a tensile strength of 2.35 MPa, a tensile strain of 630%, and a conductivity of 10 mS / cm, and remained in its original state after being taken out after being stored at -20°C for 10 hours. It can be seen that the gelatin-based hydrogel prepared in Example 2 has better anti-swelling properties, mechanical properties, conductive properties and low temperature resistance.
[0067] Example 3
[0068] This embodiment provides a preparation of a gelatin-based hydrogel, comprising the following steps:
[0069] S1. Preparation of stock solution: Weigh gelatin (G108396 gelatin, pharmaceutical grade, gelatin strength ~240gBloom, Shanghai Aladdin Biochemical Technology Co., Ltd.) and deionized water according to the mass ratio, the mass ratio of gelatin to deionized water is 15 parts:100 parts, add gelatin to deionized water, stir for 1 hour in a 60°C water bath to completely dissolve the gelatin in the deionized water, and stir at a speed of 350 rpm / min to prepare a stock solution;
[0070] S2. Preparation of mixed solution: Weigh methacrylic acid (M434201, Shanghai Aladdin Biochemical Technology Co., Ltd.), initiator and conductive material according to the mass ratio. The mass ratio of gelatin, methacrylic acid, initiator and conductive material in this embodiment is 15 parts: 15 parts: 0.01 parts: 20 parts. The initiator in this embodiment adopts 2-ketoglutaric acid (K105571, 98wt%, Shanghai Aladdin Biochemical Technology Co., Ltd.), and the conductive material adopts nanosilver solution (N196423 nanosilver solution, 1000ppm, particle size: 2nm, Shanghai Aladdin Biochemical Technology Co., Ltd.), and the weighed methacrylic acid, initiator and conductive material are dissolved in the stock solution to obtain a mixed solution. Specifically, methacrylic acid was added to the stock solution prepared in step S1, and stirred for 1 hour in a water bath at 50°C, with a stirring speed of 400 rpm / min, to prepare a premixed solution A; 2-ketoglutaric acid was added to the premixed solution A, and the stirring was continued for 2 hours in a water bath at 40°C, to prepare a premixed solution B; the nanosilver solution was added to the premixed solution B, and the stirring was continued for 2 hours in a water bath at 60°C, to obtain a mixed solution. The mixed solution was subjected to ultrasonic treatment for 0.3 hours, with an ultrasonic frequency of 40 khz and an ultrasonic power of 100 W.
[0071] S3. Preparation of hydrogel: After the ultrasonic treatment, the mixed solution is polymerized by ultraviolet light, and then immersed in an inorganic salt solution to prepare a gelatin-based hydrogel. The inorganic salt solution of this embodiment is an ammonium sulfate solution with a concentration of 30wt%. Specifically, the mixed solution after ultrasonic treatment in step S2 is poured into a polytetrafluoroethylene mold, exposed to ultraviolet light with a wavelength of 365 nanometers for 70 minutes at a temperature of 25°C for polymerization, and then immersed in an ammonium sulfate solution at a temperature of 0°C for 2 hours to finally prepare a gelatin-based hydrogel.
[0072] The gelatin-based hydrogel finally prepared in step S3 of Example 3 was tested by the same test method as in Example 1. It was found that the gelatin-based hydrogel finally prepared in step S3 of Example 3 was a multi-level pore structure, which included a three-dimensional skeleton structure and a primary pore structure surrounded by the three-dimensional skeleton structure, and also included a secondary pore structure, which was distributed on the three-dimensional skeleton structure, and the inner surfaces of the primary pore structure and the secondary pore structure were continuous and free of holes, the pore size of the primary pore structure was 30-60 μm, and the pore size of the secondary pore structure was 5-20 μm. The gelatin-based hydrogel of Example 3 was found to have a balanced swelling rate of 10%, a tensile strength of 2.65 MPa, a tensile strain of 670%, and a conductivity of 20 mS / cm. It remained intact after being taken out at -20°C for 10 hours. It can be seen that the gelatin-based hydrogel prepared in Example 3 has excellent anti-swelling properties, mechanical properties, conductive properties, and low temperature resistance.
[0073] Comparative Example 1
[0074] This comparative example provides a preparation of a gelatin hydrogel, comprising the following steps:
[0075] S1. Preparation of stock solution: Weigh gelatin (G108396 gelatin, pharmaceutical grade, gelatin strength ~240gBloom, Shanghai Aladdin Biochemical Technology Co., Ltd.) and deionized water according to the mass ratio, the mass ratio of gelatin to deionized water is 10 parts:90 parts, add gelatin to deionized water, stir for 3 hours in a 40°C water bath to completely dissolve the gelatin in the deionized water, and stir at a speed of 200 rpm / min to prepare a stock solution;
[0076] S2'. Preparation of hydrogel: Pour the stock solution prepared in step S1 into a polytetrafluoroethylene mold and keep it warm at 0°C for 2h to prepare a gelatin hydrogel.
[0077] The gelatin hydrogel finally prepared in step S2' of comparative example 1 was tested in the same manner as in example 1. Figure 4 This is a scanning electron microscope of the cross section of the gelatin hydrogel prepared in Comparative Example 1 after freeze drying. It can be seen from the observation that the internal structure of the gelatin hydrogel prepared in Comparative Example 1 includes a three-dimensional skeleton structure and a pore structure surrounded by the three-dimensional skeleton structure. The pore structure is unevenly distributed, and the pore size of the pore structure is less than 15 μm. The gelatin hydrogel prepared in Comparative Example 1 is measured to have a balanced swelling rate of 300%, a tensile strength of 0.0045 MPa, a tensile strain of 5%, and a conductivity of 0.01 mS / cm.
[0078] Comparative Example 2
[0079] This comparative example provides a preparation method of a methacrylic acid hydrogel, comprising the following steps:
[0080] S1". Preparation of mixed solution: Weigh methacrylic acid (M434201, Shanghai Aladdin Biochemical Technology Co., Ltd.), initiator, conductive material and deionized water according to the mass ratio. The mass ratio of methacrylic acid, initiator, conductive material and deionized water in this comparative example is 15 parts: 0.01 parts: 20 parts: 100 parts. The initiator of this comparative example is 2-ketoglutaric acid (K105571, 98wt%, Shanghai Aladdin Biochemical Technology Co., Ltd.), and the conductive material is a nanosilver solution (N196423 nanosilver solution, 1000ppm, particle size: 2nm, Shanghai Aladdin Biochemical Science and Technology Co., Ltd. Technology Co., Ltd.), and dissolve the weighed methacrylic acid, initiator and conductive material in deionized water to obtain a mixed solution. Specifically, methacrylic acid is added to deionized water, stirred for 1 hour in a 50°C water bath, and the stirring speed is 400rpm / min to prepare a premix A; 2-ketoglutaric acid is added to the premix A, and the stirring is continued for 2 hours in a 40°C water bath to prepare a premix B; nanosilver solution is added to the premix B, and the mixture is stirred for 2 hours in a 60°C water bath to obtain a mixed solution. The mixed solution is ultrasonically treated for 0.3 hours, the frequency of the ultrasound is 40khz, and the power of the ultrasound is 100W.
[0081] S2". Preparation of hydrogel: pour the mixed solution after ultrasonic treatment in step S1" into a polytetrafluoroethylene mold, expose it to ultraviolet light with a wavelength of 365 nanometers at a temperature of 25°C for 70 minutes for polymerization treatment, and then soak it in an ammonium sulfate solution at a temperature of 0°C for 2 hours to finally prepare methacrylic acid hydrogel.
[0082] The methacrylic acid hydrogel prepared in Comparative Example 2 was tested in the same manner as in Example 1. Figure 5 This is a scanning electron microscope of the cross section of the freeze-dried methacrylic acid hydrogel prepared in Comparative Example 2. It can be seen from the observation that the internal structure of the methacrylic acid hydrogel prepared in Comparative Example 2 includes a three-dimensional skeleton structure and a pore structure surrounded by the three-dimensional skeleton structure. The pore size of the pore structure is 20 to 100 μm, and there are no holes on the inner surface of the pore structure. The equilibrium swelling rate of the methacrylic acid hydrogel prepared in Comparative Example 2 is measured to be 280%, the tensile strength is 0.38 MPa, the tensile strain is 640%, and the conductivity is 16 mS / cm.
[0083] Comparative Example 3
[0084] The difference between Comparative Example 3 and Example 1 is that, in the step S2. of preparing the mixed solution, the mixed solution is subjected to ultrasonic treatment for 0.3 h, the ultrasonic frequency is 60 khz, and the ultrasonic power is 70 W. The remaining preparation steps are the same as those in Example 1, and a gelatin-based hydrogel is prepared.
[0085] The gelatin-based hydrogel finally prepared in step S3 of comparative example 3 was tested in the same manner as in example 1. Figure 6 The scanning electron microscope of the cross section of the gelatin-based hydrogel prepared in Comparative Example 3 after freeze drying shows that the internal structure of the gelatin-based hydrogel prepared in Comparative Example 3 includes a three-dimensional skeleton structure and a pore structure surrounded by the three-dimensional skeleton structure. The pore size of the pore structure is 20 to 100 μm, and unevenly distributed holes of less than 15 μm are further formed on the inner surface of the pore structure. The gelatin-based hydrogel finally prepared in step S3 of Comparative Example 3 was measured to have an equilibrium swelling rate of 80%, a tensile strength of 1.9 MPa, a tensile strain of 610%, and a conductivity of 8 mS / cm.
[0086] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to this application.
Claims
1. A gelatin-based hydrogel with a multi-level pore structure, characterized in that: The gelatin-based hydrogel is prepared from raw materials including gelatin, methacrylic acid, an initiator and a conductive material, wherein the mass ratio of the gelatin, methacrylic acid, the initiator and the conductive material is 5-30:5-50:0.0005-0.05:3-80, and the gelatin-based hydrogel includes a three-dimensional skeleton structure and a primary pore structure surrounded by the three-dimensional skeleton structure, and also includes a secondary pore structure, wherein the secondary pore structure is distributed on the three-dimensional skeleton structure, and the inner surfaces of the primary pore structure and the secondary pore structure are continuous and free of holes, the pore diameter of the primary pore structure is 30-100 μm, and the pore diameter of the secondary pore structure is 5-25 μm; The gelatin-based hydrogel comprises the following preparation steps: S1. Preparation of stock solution: Weigh gelatin according to the mass ratio and dissolve it in deionized water to prepare a stock solution, wherein the mass ratio of gelatin to deionized water is 5~30:45~300; S2. Preparation of a mixed solution: Weighing methacrylic acid, an initiator and a conductive material according to a mass ratio, and dissolving the methacrylic acid, the initiator and the conductive material in the stock solution to obtain a mixed solution, wherein the mixed solution is subjected to ultrasonic treatment, wherein the frequency of the ultrasonic treatment is 30 to 50 khz, and the power of the ultrasound is 100 to 150 W; S3. Preparation of hydrogel: The mixed solution after ultrasonic treatment is polymerized by ultraviolet light, and then immersed in an inorganic salt solution to prepare a gelatin-based hydrogel with a multi-level pore structure.
2. The gelatin-based hydrogel with a multi-level pore structure according to claim 1, characterized in that: The mass ratio of the gelatin, methacrylic acid, initiator and conductive material is 8-20:8-30:0.0008-0.03:8-40.
3. The gelatin-based hydrogel with a multi-level pore structure according to claim 1 or 2, characterized in that: The pore size of the primary pore structure is 30-80 μm, and the pore size of the secondary pore structure is 5-20 μm.
4. The gelatin-based hydrogel with a multi-level pore structure according to claim 1 or 2, characterized in that: The conductive material is at least one of PEDOT:PSS, nanosilver, carbon nanotubes, carbon nanosheets, MXenes or graphene.
5. The gelatin-based hydrogel with a multi-level pore structure according to claim 1 or 2, characterized in that: The initiator is at least one of 2-ketoglutaric acid, glutaraldehyde or ammonium persulfate.
6. The gelatin-based hydrogel with a multi-level pore structure according to claim 1 or 2, characterized in that: The gelatin-based hydrogel has a tensile strength of 2.35-2.65 MPa, a tensile strain of 630%-670%, a balanced swelling ratio of 8%-11%, and a conductivity of 10-20 mS / cm.
7. The gelatin-based hydrogel with a multi-level pore structure according to claim 1, characterized in that: In step S1, the gelatin is added to the deionized water, and stirred in a water bath at 40-60° C. for 0.3-6 h to completely dissolve the gelatin in the deionized water to prepare the stock solution, with the stirring speed being 50-500 rpm.
8. The gelatin-based hydrogel with a multi-level pore structure according to claim 1, characterized in that: In step S2, the methacrylic acid is added to the stock solution, and stirred for 0.3-6 hours in a water bath at 40-60° C., with a stirring speed of 50-500 rpm, to prepare a premixed solution A; the initiator is added to the premixed solution A, and the stirring is continued for 0.3-6 hours in a water bath at 40-60° C., to prepare a premixed solution B; the conductive material is added to the premixed solution B, and the stirring is continued for 0.3-6 hours in a water bath at 40-60° C., to prepare the mixed solution.
9. The gelatin-based hydrogel with a multi-level pore structure according to claim 1, characterized in that: In step S3, the mixed solution is irradiated with the ultraviolet light of 300-400 nanometers for 50-100 minutes, and then immersed in the inorganic salt solution for 1-5 hours, wherein the concentration of the inorganic salt solution is 20-40 wt%.
Citation Information
Patent Citations
Hydrogel materials and discloses polypyrrole nano composite conductive hydrogel and preparation method thereof
CN109627461A
Cold-induced high-strength conductive curdlan eutectic hydrogel as well as preparation method and application thereof
CN116217970A
Hydrogel with hemostatic and anti-inflammatory effects as well as preparation method and application thereof
CN116870243A
KR20220167644A